2010
DOI: 10.1179/174328409x439088
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of 308 stainless steel insert with A319 aluminium casting alloy

Abstract: In the metallurgical connection of aluminium alloys to steels, it is important to restrain the formation and growth of hard and brittle intermetallic phases at the aluminium/steel interface to enhance the mechanical behaviour of the joint. The influence of two coating materials, electroless plated copper (for 20 and 40 min) and galvanised zinc (at 480 and 550°C), on the quality of the interface between 308 stainless steel and A319 aluminium matrix was investigated. Copper led to the formation of a compact, sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…It is observed that Zn coatings on steel surfaces have many beneficial influences on aluminum/steel bimetal joining characteristics. However, interestingly, many studies on aluminum/steel joining except diffusion bonding processes as well as the present study have reported that Zn atoms are hardly detected at interfacial intermetallic phases [12,13,28,39]. The reasons for that are tried to be explained in relation to the behavior of Zn coating layer as follows.…”
Section: Accepted Manuscriptmentioning
confidence: 60%
See 3 more Smart Citations
“…It is observed that Zn coatings on steel surfaces have many beneficial influences on aluminum/steel bimetal joining characteristics. However, interestingly, many studies on aluminum/steel joining except diffusion bonding processes as well as the present study have reported that Zn atoms are hardly detected at interfacial intermetallic phases [12,13,28,39]. The reasons for that are tried to be explained in relation to the behavior of Zn coating layer as follows.…”
Section: Accepted Manuscriptmentioning
confidence: 60%
“…This method is a very attractive manufacturing process for automotive components with complex shapes due to the benefits of cost-effectiveness, high production rate, and net shaping capability [11]. Despite these many benefits, it still remains difficult to get the aluminum to firmly join to steel inserts because of oxide scales on steel surface and large differences in the thermal-physical properties between those two metals, such as melting point and thermal expansion coefficient, which lead to poor wetting and metallurgical bonding [12,13]. Especially, in a form in which aluminum and steel are layered in parallel, rather than a form in which steel is embedded in aluminum, their joining becomes much more difficult because the shrink fitting effect is not available.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction layer thickness increased significantly (80 m) after heat treatment at 540 °C for 2h with cracks appearance that, de facto, weekend the interface bonding strength. The composition and microstructure of intermetallic compounds (IMC) formed at the interface between aluminum alloy AA4343 and stainless steel SUS316 upon annealing at 550 •C for 1h to 20h and at 610 •C for 15min to 10h were recently studied by Zhang et al [32]. The reaction layer after solution at 550 °C for 10h was constituted above all by τ10(Al4Fe1.7Si) and η(Al 5 Fe 2 ); its growth kinetics followed the rational equation x = (kt) n , where x is the layer thickness, t is the time and k and n are two constants.…”
Section: Introductionmentioning
confidence: 99%